PREPEGAN TRADITION IN BANDUNGAN SEMARANG: AN EFFORT TO INVENTORY OF GRASSROOT CULTURE - Zein Muchamad Masykur (Khatulistiwa, 2023)
Tradition is not just a question of 'how the custom is done' or 'why this needs to be done'. However, at least, these methods and reasons can be passed down completely to the next generation. It can be understood well, not only as a cultural heritage, but also as a living value in the society they live in. Understanding of traditional values will be biased, degraded, and even fade or disappear altogether if no one writes them down. Writing is an inventory of civilizations. Even if it's just a fragment, it's still important. This study does not have a complicated goal such as analyzing patterns of cultural integration, or interpreting traditional symbols. Just a small effort to write down the cultural phenomena that occur in the environment around the researcher. Not a culture of elite society, but the culture of farmers, middlemen, traders, and other lower class groups. At least, through this paper, the researcher hopes that there will be more who conduct studies on grassroots culture.Kata kunci: Budaya, Inventarisasi, Akar Rumput